Field Trials with Toxic Bait for the Control of the Brown Garden Snail (Helix aspersa, Muller) - Schwartz, A.; Siebert, M.W. (South African Journal of Enology and Viticulture, 2017)
Standard and new snail baits were evaluated for the control of the brown garden snail, Helix aspersa Miiller in a vineyard. As a ground treatment, the proprietary bait Sluggem (carbaryl/metaldehyde) gave satisfactory control, whereas Mesurol (methiocarb) bait or Mesurol (methiocarb) wettable powder mixed with bran and water were less successful. The new proprietary bait formulation, Suprasnail (metaldehyde), was effective on the ground and arboreally (on the arms of the vine).